Repeat Surgery for Vestibular Schwannomas: An Institutional Case Series - Nandoliya, Khizar R.; Winterhalter, Emily J.; Karras, Constantine L.; Khazanchi, Rushmin; Youngblood, Mark W.; Texakalidis, Pavlos; Chandler, James P.; Magill, Stephen T. (Journal of Neurological Surgery Reports, 2023)
Introduction Vestibular schwannomas (VSs) are treated with microsurgery and/or radiosurgery. Repeat resection is rare, and few studies have reported postoperative outcomes. The objective of this study was to describe clinical characteristics and outcomes in patients undergoing repeat surgery for VS.Methods All adult (≥ 18 years) patients undergoing VS resection between 2003 and 2022 at our institution were retrospectively reviewed to identify patients who underwent repeat surgery of an ipsilateral VS following prior gross-total (GTR) or subtotal resection. Patient, radiographic, and clinical characteristics were reviewed. Primary outcomes were postoperative tumor volume, extent of resection, postoperative cranial nerve deficits, and time to further tumor progression.Results Of 102 patients undergoing VS resection, 6 (5.9%) had undergone repeat surgery. Median (range) follow-up was 20 (5–117) months. Three patients were female. Median age was 56 (36–60) years. Median pre- and postoperative tumor volumes were 8.2 (1.8–28.2) cm3 and 0.4 (0–3.8) cm3. GTR was achieved in two patients. Four patients had higher House-Brackmann scores at last follow-up, but none had tumor progression.Conclusion In this small cohort of patients, repeat resection of recurrent or progressive VS can effectively reduce tumor volume with acceptable perioperative outcomes.
Keywords: acoustic neuroma; microsurgery; repeat surgery; vestibular schwannoma